Supporting Community Partners in Reducing HIV-Related Health Disparities: Technical Assistance Across a Spectrum of Intensity - Daryl Mangosing MPH; Gertrude Kumalo-Sakutukwa MSc, MSW; Beth Bourdeau PhD; Greg Rebchook PhD; Marguerita Lightfoot PhD; Janet J Myers PhD, MPH (SAGE Publishing, 2022)
The HIV epidemic remains a public health threat in the U.S., and the dissemination and implementation of evidence-based prevention and care programs are critical to addressing significant HIV health disparities. The provision of technical assistance (TA) to program providers and evaluators is key for uptake of these programs. The University of California San Francisco Prevention Research Center (UCSF PRC) model for TA delivery uses topics and strategies adapted to address HIV health disparities for a global audience. This model specifically matches TA requests to a TA provider who has expertise in that area upon receiving a request through various communication channels. Areas of expertise include research methods, community engagement strategies, interventions, and Implementation Sciences. Our evaluation of diverse TA services indicates that on-demand TA is effective for light-touch requests and well-suited for moderate to intensive requests. The model is a promising, broad-reaching, and responsive alternative for providing TA to a multitude of HIV workforce recipients.